Conditions Under Which Glutathione Disrupts the Biofilms and Improves Antibiotic Efficacy of Both ESKAPE and Non-ESKAPE Species - Das, Theerthankar; Paino, Denis; Manoharan, Arthika; Farrell, Jessica; Whiteley, Greg; Kriel, Frederik H.; Glasbey, Trevor; Manos, Jim (Frontiers in Microbiology, 2019)
Bacterial resistance to antibiotics has significantly increased in recent decades, raising concerns in hospital and community settings. Novel, innovative strategies are needed to combat resistance and to diminish the likelihood of recurrent transmission. In this study, we investigated whether glutathione (GSH) can act as a biofilm disruptor, and enhance antibiotic effectiveness against various bacterial pathogens. Biological levels (10mM) of GSH did not have a significant effect in inhibiting growth or disrupting the biofilm in four out of six species tested. However, exposure to 30mM GSH showed >50% decrease in growth for all bacterial species, with almost 100% inhibition of Streptococcus pyogenes and an average of 94 - 52% inhibition for Escherichia coli, Methicillin-resistant Staphylococcus aureus (MRSA) and Methicillin-sensitive S. aureus (MSSA) and multi-drug resistant Acinetobacter baumannii (MRAB) isolates, respectively. Klebsiella pneumoniae and Enterobacter sp. isolates were however, highly resistant to 30mM GSH. With respect to biofilm viability, all species exhibited a >50% decrease in viability with 30mM GSH, with confocal imaging showing considerable change in the biofilm architecture of MRAB isolates. The mechanism of GSH-mediated biofilm disruption is possibly due to a concentration-dependent increase in GSH acidity that triggers cleaving of the matrix components. Enzymatic treatment of MRAB revealed that eDNA and polysaccharide are essential for biofilm stability and eDNA removal enhanced amikacin efficiency. Combination of GSH, amikacin and DNase-I showed the greatest reduction in MRAB biofilm viability. Additionally, GSH alone and in combination with amikacin shown to foster human fibroblast cell (HFF-1) growth and confluence while inhibiting MRAB adhesion and colonization.